Kompetensi Manajerial Kepala Madrasah Dalam Peningkatan Kinerja Guru di MTs Miftahul Ulum Cermenan Ngoro Jombang - Beny Sintasari; Baiq Khaerani (At Tadbir: Islamic Education Management Journal, 2023)
This research aims to analyze the managerial competence of madrasah heads in the context of improving teacher performance. Madrasah heads have a very important role in supporting and motivating teachers to achieve better educational outcomes. In addition, an effective madrasa head must have good communication skills, wise decision-making abilities, and be able to create a positive work environment. Managerial competency also includes the ability to motivate and develop teacher staff, as well as manage resources efficiently. Good teacher performance is a key factor in achieving the goals of quality madrasa education. The research objective is first to describe the managerial competence of madrasah heads in improving teacher performance at MTs Miftahul Ulum Cermenan. Second, teacher performance at MTs Miftahul Ulum Cermenan. This research method is qualitative with data collection techniques using interviews, observation and documentation. The results of this research indicate that the managerial competence of madrasah heads involves various aspects, including the ability to plan, organize, implement and control. The performance of teachers at MTs Miftahul Ulum Cermenan has good performance. Teachers are able to create learning tools, manage the learning process effectively by utilizing media and school facilities, and carry out assessments. The managerial competence of madrasah heads has been able to improve teacher performance because they have implemented madrasah indicators which refer to madrasah input, process, output and outcomes.